PENGARUH KUALITAS AUDIT TERHADAP KEMAMPUAN INVESTOR MEMPREDIKSI LABA DI MASA DEPAN - Kinantya Komala Nur Shabrina; Fuad Fuad (Diponegoro Journal of Accounting, 2013)
The purpose of this research is to examine the impact of audit quality on the investor’s ability to predict future earnings and to examine investor’s ability to predict future earnings for profitable firms and unprofitable firms. This research is a replication of the study by Hussainey (2009). The population of this research are 414 manufacture companies which is listed in Indonesia Stock Exchange period 2008-2010. Samples were selected by purposive sampling method  and finally obtained  180 manufacture companies  that fulfill the criterias. Data were analyzed using Collins et al. (1994) return-future earnings regression model.